2018
DOI: 10.1016/j.engfailanal.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the influence of hydrogen on some commercial DP, Q&P and TWIP advanced high-strength steels during automobile service

Abstract: The hydrogen influence was evaluated (A) for laboratory conditions with hydrogen concentrations larger than in service, and (B) at substantial loading rates to simulate a crash. Hydrogen in the studied laboratory conditions caused minimal influence for 980DP and 1200DP, and some influence for 980DP-650YS, 980DP-700YS, 980QP and 950TW. Simulated crash situations caused some influence for 980DP, 980QP and 950TW; their properties quickly reverted after the end of hydrogen charging. Two new mechanisms are proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 58 publications
(160 reference statements)
1
18
0
Order By: Relevance
“…However, these AHSS may be influenced by hydrogen [5], which may cause decreased mechanical strength and decreased ductility [6][7][8][9][10]. Our previous research [11,12] showed that the influence of hydrogen on some commercial DP, Q&P and TWIP steels was manifested by (i) a somewhat decreased yield strength (by 1% to 20%), (ii) a reduced ductility caused by hydrogen assisted fracture processes occurring after the onset of necking at the ultimate tensile strength of the steel. Furthermore, the magnitude of the hydrogen influence increased with increasing strength, decreasing applied stress rate, and increasing hydrogen fugacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these AHSS may be influenced by hydrogen [5], which may cause decreased mechanical strength and decreased ductility [6][7][8][9][10]. Our previous research [11,12] showed that the influence of hydrogen on some commercial DP, Q&P and TWIP steels was manifested by (i) a somewhat decreased yield strength (by 1% to 20%), (ii) a reduced ductility caused by hydrogen assisted fracture processes occurring after the onset of necking at the ultimate tensile strength of the steel. Furthermore, the magnitude of the hydrogen influence increased with increasing strength, decreasing applied stress rate, and increasing hydrogen fugacity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, inclusions have been also shown to decrease the hydrogen embrittlement (HE) resistance of steels [9,15,16]. This literature indicates that it is useful to analyse the role of microstructure on the influence of hydrogen on the commercial DP, Q&P and TWIP steels studied in our prior research [11,12,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen caused a reduction in the UTS but fracture only occurred once the applied stress had reached the UTS [11]. This indicates that some mechanisms that promote subcritical cracks, often associated with hydrogen embrittlement, are not directly applicable [11,15]. ii.…”
Section: Hydrogen Embrittlementmentioning
confidence: 99%
“…ii. Hydrogen assisted micro-fracture (HAM): Hydrogen causes a change in microfracture mode from a ductile to brittle fracture that is initiated at the specimen surface during the final fast fracture [15].…”
Section: Hydrogen Embrittlementmentioning
confidence: 99%
See 1 more Smart Citation